(untitled) (Journal of Human Sciences, 2021)
The study aims to diagnose the authenticity of Arabic language in Arab societies, and to identify the language role in Arab media discourse. Hence the language functions as the medium of thought and expression where it has the capacity to influence and bring about growth in other societies. In addition to that it plays an important role in developing the skills of Arab media professionals enabling them to formulate an influential media discourse. The researcher uses a descriptive approach in order to describe the problem of the study and its analytical approach. There were a number of results. The results show that (86%) of the sample believe in the importance of language in media discourse and its role in developing the skills of Arab media professionals, compared to (14%) who do not believe in its importance. The study shows that (89%) of the sample believe in the importance of Arabic language role in developing the skills of media professionals. In contrast, (11%) of the sample do not believe in the importance of its role. The results also show that (85%) of the sample prefer the Arabic language to foreign languages to study and learn media science, and also the results show that (50.5%) of the sample are specialists in public relations. In addition, the results show that (55%) of the sample believe that job employment is preferable to graduates from Arab programs, whereas (39.5%) believe that preference is given to graduates from English programs, and there are (5.5%) who see preference in employment is to graduates from other programs.